Penggunaan Media Lesedomino dalam Peningkatan Kosakata Bahasa Jerman - Aurelia Astuti Umar; Abdul Kasim Achmad (Universitas Negeri Makassar, 2022)
Abstract. This research is Classroom Action Research which consist of two cycles. This study aims to determine the planning, process, and results of the use of Lesedomino Media in Increasing the German Vocabulary of Class X of SMAK St. Gregorius Reok. This research consist of quantitative data and qualitative data. Quantitative data was obtained through the result of vocabulary test in cycle I and cycle II and qualitative data was obtained through observation. The data were analysed using the percentage technique. The result showed the average score obtained by students in the first cycle reached 65,5% and the second cycle reached 79%. These result indicate that the use of Lesedomino media can improve vocabulary of Class X SMAK St. Gregorius Reok.Keywords: Lesedomino, Improvement, Vocabulary, German